Heterolytic (2 e) vs Homolytic (1 e) Oxidation Reactivity: N−H versus C−H Switch in the Oxidation of Lactams by Dioxirans. Issue 2 (6th December 2016) - Annese, Cosimo; D'Accolti, Lucia; Fusco, Caterina; Licini, Giulia; Zonta, Cristiano
Abstract: Dioxiranes are powerful oxidants that can act via two different mechanisms: 1) homolytic (H abstraction and oxygen rebound) and 2) heterolytic (electrophilic oxidation). So far, it has been reported that the nature of the substrate dictates the reaction mode independently from the dioxirane employed. Herein, we report an unprecedented case in which the nature of the dioxirane rules the oxidation chemoselectivity. In particular, a switch from C−H to N−H oxidation is observed in the oxidation of lactams moving from dimethyl dioxirane (DDO ) to methyl(trifluoromethyl)dioxirane (TFDO ). A physical organic chemistry study, which combines the oxidation with two other dioxiranes methyl(fluoromethyl)dioxirane, MFDO, and methyl(difluoromethyl)dioxirane, DFDO, with computational studies, points to a diverse ability of the dioxiranes to either stabilize the homo or the heterolytic pathway. Abstract : Variation of the electronic features of a series of dioxiranes results in a sharp switch in the oxidation chemoselectivity of lactam rings. A physical organic chemistry study, which combines the oxidation with two other dioxiranes methyl(fluoromethyl)dioxirane and methyl(difluoromethyl)dioxirane with computational studies, points to a diverse ability of the dioxiranes to either stabilize the homo or the heterolytic pathway.